Unmet care needs of children with ADHD - Vijverberg, Richard (PLoS One, 2020)
BACKGROUND: Non-compliance to, or drop-out from treatment for childhood ADHD, result in suboptimal outcome. Non-compliance and drop-out may be due to mismatches between patients' care needs and treatments provided. This study investigated unmet care needs in ADHD patients. Unmet needs were assessed in two different treatment settings (general outpatient setting versus youth-ACT). Youth-ACT treatment is an intensive outreach-oriented treatment for patients with severe psychiatric and psychosocial problems. Comparison of a general outpatient sample with a youth-ACT sample enabled us to assess the influence of severity of psychiatric and psychosocial problems on perceived care needs. METHODS: Self-reported unmet care needs were assessed among 105 ADHD patients between 6 and 17 years of age in a general outpatient (n = 52) and a youth-ACT setting (n = 53). RESULTS: ADHD patients most frequently reported unmet needs regarding mental health problems, information on diagnosis/treatment, and future prospects. Outpatients differed from youth-ACT patients with respect to 30% of the unmet care needs that were investigated. Outpatients perceived more unmet needs regarding information on diagnosis/treatment (p = 0.014). Youth-ACT patients perceived more unmet needs concerning medication side effects (p = 0.038), quality and/or quantity of food (p = 0.016), self-care abilities (p = 0.016), regular/suitable school or other daytime activities (p = 0.013), making and/or keeping friends (p = 0.049), and future prospects (p = 0.045). CONCLUSIONS: Focusing treatment of ADHD patients on unmet needs may reduce non-compliance and drop-out. In clinical practice, systematic assessment of unmet care needs in all ADHD patients may be warranted, e.g. using the CANSAS questionnaire during the screening/intake phase.